Cerebral Venous Thrombosis in Evan’s Syndrome: An Unusual Presentation - MH, Cheng; TAB, Norzila (IIUM Medical Journal Malaysia, 2016)
Cerebral Venous Thrombosis in patients with Evan’s Syndrome of autoimmune hemolytic anemia is rare. The common neurological symptoms are headaches, vision loss, dyslexia without agraphia, motor aphasia, unilateral upper limb weakness and papilloedema. We present a case report of a lady with a known case of Evan’s Syndrome whom presented with severe anemia and unilateral right sided hemiparesis with right facial weakness. Plain and Contrast enhanced CT brain showed bilateral high parietal white matter edema with venous thrombosis in the right transverse and superior sagittal venous sinuses. At the time of the diagnosis, she was in hematological remission.